PENGARUH EFEKTIVITAS PETUGAS PENDAMPING PROGRAM KELUARGA HARAPAN TERHADAP KESEJAHTERAAN KELUARGA PENERIMA MANFAATDI KELURAHAN MAYANG MANGURAI - Zuria, Aminatu; Putra, Redi Indra (SJEE (Scientific Journals of Economic Education), 2021)
AbstractThis study aims to 1) to see the description of the effectiveness of the assistant officers of the family of hope program (PKH) on the welfare of the beneficiary families (KPM) in the Mayang Mangura village, 2) to see the effect of the effectiveness of the assistant officers of the family of hope program (PKH) on the welfare of the beneficiaries ( KPM) in the village of Mayang mangurai. The research used a quantitative approach based on the philosophy of positivism, used in certain populations or samples. The technique of collecting data was generally random. Data analysis in this study consisted of validity, reliability, simple regression, normality, homogeneity and TCR. From the results of the study, it can be concluded that the regression equation is Y = a+ bx = 16,078+ 0,508 X. The equation is in accordance with the simple linear regression formula, namely Y=a+bx, where Y is the symbol of the dependent variable, a is a constant, b is the regression coefficient for the independent variable. (X). Thus, it can be concluded from the results of the t-test, that there is an influence between variable Y on variable X, in other words accepting Ha, namely: the effect of the effectiveness of the assistant officers of the Family Hope Program on the Welfare of Beneficiary Families in Mayang Mangurai. The results of the study on the Effectiveness of Assistance Officers Based on the data that has been filled in by the respondents, it is known that the assistant officers are still less effective in providing guidance to the beneficiary families. because from filling out the questionnaire that has been filled out by the community, they state that they are in a poor level of welfare.Keywords: Officer Effectiveness, Family Welfare.